Assessment Based on Higher Order Thinking Skill on SKI Learning - Yelfi Dewi S; Moh In'ami; Alina Audia; Masrukhin Masrukhin (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research was conducted to know the assessment instrument for SKI subjects at a state Madrasah Aliyah in Jepara; piloted HOTS-based assessment instrument, and the results of the HOTS-based assessment on SKI subjects. This type of field research is quantitative. This research is field research, namely direct observation of the object under study. Collecting data through interviews, observation, and documentation. The approach used in conducting research is empirical. The instruments used in the SKI subject are oral tests, multiple choice, and assignments. Meanwhile, the researchers used multiple choice and essay test instruments to obtain HOTS-based assessment results. Then the researcher tested the feasibility of the questions with expert validity and the validity and reliability of the items. The final total of 4 multiple choice questions and two essays obtained the result. The HOTS-based assessment was applied to SKI subjects even though all KD could not be included. The findings of this study also show the results of the HOTS-based evaluation with 23 students in the high group, 60 students in the medium group, and 13 students in the low group.